Penerapan Teori Pada Hakikatnya Dalam Menafsirkan Tindak Pidana Narkotika - Susilo, Erwin; Sembiring, Eddy Daulatta; Asih, Wigati Taberi (Nagari Law Review, 2024)
Narcotics crimes are classified as a serious crime. Therefore, good law enforcement is needed to overcome crime, primarily related to the implementation of articles of narcotic crime in the trial. There is a significant urgency to implement law enforcement methods to handle narcotics crimes. This study explores the method of interpretation options for judges in granting a judgment in case an act is proven valid and convincingly guilty in narcotics cases. This study uses normative legal research methods or doctrinal legal research, in which the researchers will study the application of criminal offenses by law enforcers. The researcher is guided by the objectives of punishment adopted by the related regulations, criminal procedural law, and material criminal law. This study finds alternative interpretations for judges in determining which articles are legally and convincingly proven guilty of narcotics crimes as regulated by the law. Thus, this research provides insight into the importance of integrating theory and practice in criminal law for narcotics. The study also recommends strategies to increase the effectiveness of just law enforcement in narcotics cases.